Individual and Collaborative Semiotic Work in Document Design - Hiippala, Tuomo (HERMES - Journal of Language and Communication in Business, 2016)
This article examines the concepts of agency, transformation and transduction in the context of document design. These concepts have been previously used to describe communicative actions and sign-making among individuals: whereas agency focuses on the individual’s capabilities as a sign-maker, transformation and transduction describe how individuals transform meanings within one mode of communication or from one mode to another. Organizational communication, however, is rarely an individual effort, particularly in corporate settings: producing multimodal documents that communicate on behalf of entire organizations, such as annual reports, constitutes a collaborative effort involving a variety of specialists, such as concept planners, copywriters and graphic designers. In the age of increasing specialization, this kind of collaborative semiotic work raises questions about agency, transduction and transformation. In this context, the concepts of agency and transmodality, which emphasize the individual, appear to have reduced explanatory power. This leads to the central question of this article, that is, how can the collaborative design process be captured and how does it affect the multimodal structure of annual reports? By analyzing an annual report published by Finnair and interviewing its designers, this article aims to illuminate the design process and its consequences to the document in question.